Effects of surgical trauma and intraoperative blood loss on tumour progression - Jin, Xiaoqin; Han, Han; Liang, Qilian (Frontiers in Oncology, 2024)
Surgery is the primary treatment of choice for tumours, and improves prognosis, prolongs survival and is potentially curative. Previous studies have described the effects of anaesthesia and changes in the neuroendocrine, circulatory and sympathetic nervous systems on postoperative cancer progression. There is growing evidence that intraoperative blood loss is an independent prognostic factor for tumour recurrence, postoperative inflammation is a predictor of cancer prognosis, and immunosuppressive status correlates with the degree of surgical damage. This paper outlines the potential mechanisms by which blood loss, surgical trauma and postoperative immunosuppressive status contribute to tumour growth and recurrence by reducing intraoperative haemorrhage and perioperative immunotherapy, thereby reducing tumour growth and recurrence, and improving long-term prognosis.